Longitudinal changes in bone mass in children with cystic fibrosis: effect of size adjustment using bone mineral apparent density. (29th September 2015) - Williams, J; Crabtree, N; Benden, C; Suri, R; Jaffe, A; Fewtrell, M
Abstract : Background: Patients with cystic fibrosis (CF) are at risk of poor growth, suboptimal bone mineralisation and osteoporosis. Bone health monitoring is recommended from age 10 years; however, DXA machine-derived bone mineral density (BMD) SD scores (sds) do not fully adjust for body size and may give deceptive results for children small for age. Objective: To assess (1) trends in BMD over time; (2) effect of size adjustment using bone mineral apparent density (BMAD). Methods: 56 children (32 girls) with CF had DXA measurements (GE Lunar Prodigy) of the lumbar spine (L2–L4) at baseline (age 7–12 years) and 2 years, providing BMD sds for age and sex; 34 children (19 girls) were measured at 4 years. BMAD was calculated as BMC/BA 1.5 and BMAD sds derived for age and sex using UK reference data. Results: Compared to reference data, CF patients were significantly shorter (mean (SD); height sds; boys −0.7 (1.1), girls −0.7 (1.2), p<0.01) and girls were lighter (weight sds; −0.6 (1.2), p<0.01). Mean baseline BMD sds was <0 and fell significantly and progressively at 2 and 4 year follow-up, especially in girls; (−0.72 (1.13), −1.06 (0.93), −1.13 (1.27). Apparent bone deficits were reduced when expressed as BMAD sds, although scores remained significantly <0 in girls; (−0.62 (1.01), −0.70 (0.89), −0.60 (1.02)). Seven children had BMDsds less than −2 with normal BMAD sds; eight children had both BMDsds and BMAD sds less than −2. 20 children had BMAD sds at least 0.5 sds lower than BMDsds. Two children <10 years had BMD and BMAD sds less than −2. Conclusion: Mean BMD sds was low and fell progressively with age especially in girls. Although use of BMAD sds reduced the apparent bone deficit and may have avoided mis-diagnosis in some children small for age, in others BMAD sds was lower than BMD sds suggesting BMD sds does not always underestimate bone mass. Two children <10 years had low BMAD sds but would not have been scanned under current guidelines indicating the need for a flexible approach to their implementation.